Krisis Identitas Nasional sebagai Tantangan Generasi Muda di Era Globalisasi - Sakdiyah Sakdiyah; Widna Widna; Sasmi Nelwati (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
National Identity Crisis as a Challenge for the Young Generation in the Era of Globalization. A national identity is a marker of an identity belonging to and attached to a nation or a country that can be distinguished from another. National identity must be able to preserve the existence and survival of a nation because it contains cultural values that have similar characteristics, physical characteristics, ideals and goals. National identity, therefore, is vital for implanting and applying to daily life as to the future of nations. In today's times of globalization, most aspects of life have changed. That certainly brings with it both the good and the bad effects that society has to face. Many foreign cultures are moving in and developing within communities. It can, of course, threaten the national identity of the nation. National identity crises can occur especially in the younger generation, which can very easily be affected by the current globalization. Awareness of the importance of keeping cultural values as national identity began to fade. To that end, efforts must be made to foster a renewed awareness of national identity, which is appropriate to the development of nowaday's science and technology.